An Error Estimate of a Modified Method of Characteristics Modeling Advective-Diffusive Transport in Randomly Heterogeneous Porous Media (CSIAM Transactions on Applied Mathematics, 2022)
We analyze a stochastic modified method of characteristics (MMOC) modeling advective-diffusive transport in randomly heterogeneous porous media. Under thelog-normal assumption of the porous media and the finite-dimensional noise assumption that leads to unbounded diffusivity, we prove an optimal-order error estimate forthe stochastic MMOC scheme. Numerical experiments are presented to substantiatethe numerical analysis.